ANALISIS RESIKO BAHAYA KESELAMATAN DAN KESEHATAN KERJA (K3) ALAT BERAT PADA PROYEK TRAIN LOADING STATION 6 DAN 7 SUMATERA SELATAN - Revita Wulandari; Septia Dwi Cahyani; Yusup Saktiawan (Jurnal Multidisipliner Kapalamada, 2026)
This study aims to analyze OHS hazard risks associated with heavy equipment operations at Train Loading Station Projects 6 and 7 in South Sumatra. This study employed a descriptive design with a qualitative approach. The research subjects consisted of 10 selected participants. Data were collected through observation, interviews, questionnaires, and document review. Risk analysis was conducted using the HIRADC approach, which includes hazard identification, risk assessment, and risk control, based on the OHS guidelines implemented at the project site.The results indicate that multiple hazards are associated with heavy equipment operations, including being struck by equipment, caught-in/between incidents, being hit by falling materials, and equipment overturning. The identified risk levels ranged from moderate to high, influenced by unsafe acts and unsafe working conditions. Recommended risk control measures include the implementation of the hierarchy of controls, such as engineering improvements, enhanced supervision, OHS training, and consistent use of personal protective equipment (PPE).